Angular-stable polarization rotator - Qasim, Ali (2014)
A new polarization rotator based on a recently proposed 3-D frequency selective structure (FSS) is designed. The rotation is an added function to the band-reject FSS, which is built using an array of parallel plate waveguides. The device exploits an L-shaped slot to generate a 90° rotated E-field component at the output. An example is designed here, operating at 10 GHz, with a half-power (3-dB) fractional bandwidth of 2.7% for the transmission coefficient of the rotated field. The insertion loss is 1.3 dB at the resonant frequency. The proposed rotator exhibits good stability over a large range of oblique incidence. The operating principle of the L-slot is explained, along with an illustration of the field behavior, and the design details are briefly discussed.